EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KARET DI KECAMATAN WANARAYA, KABUPATEN BARITO KUALA PROVINSI KALIMANTAN SELATAN - Jumainia Nur Saidah; Deasy Arisanty; Sidharta Adyatma (JPG (Jurnal Pendidikan Geografi), 2015)
This research entitled evaluation on appropriateness of land for Rubber Plant in Wanaraya Subdistrict, Barito Kuala Regency, South Kalimantan Province. The objective of this research is to know the level of land appropriateness for rubber plant in Wanaraya Subdistrict, Barito Kuala Regency, South Kalimantan Province.Population and sample of this research were same, which taken from the amount of land in Wanaraya Subdistrict, Barito Kuala Regency, South Kalimantan Province that is 16 lands. The lands are taken from overlaying of land form map, map of the kinds of land, map of land slope, and map of using  land which taken from satellite imaginery and Earth map.The result showed that land matching method in Wanaraya Subdistrict, Barito Kuala Regency, South Kalimantan Province had 2 land appropriateness classes, i.e S2 (appropriate enough) and N2 (very inappropriate), S2 has diveider , i.e temperature, dry months, drainage, water pH, salinity, and danger of flooding; and N2 has diveider temperature and salinity. Land scoring method in Wanaraya Subdistrict, Barito Kuala Regency, South Kalimantan Province included in S1 class of land very suitable. Temperature can not be changed or repaired, the bad drainage can be repaired by prosessing of land, such as manufacturing of drainage channels or planting rubber trees on a mound of soil or soil that has been elevated.Keywords: land evaluation, rubber tree, land appropriateness class